Bioorthogonal Enzymatic Activation of Caged Compounds. Issue 45 (10th September 2015) - Ritter, Cornelia; Nett, Nathalie; Acevedo‐Rocha, Carlos G.; Lonsdale, Richard; Kräling, Katja; Dempwolff, Felix; Hoebenreich, Sabrina; Graumann, Peter L.; Reetz, Manfred T.; Meggers, Eric
Abstract: Engineered cytochrome P450 monooxygenase variants are reported as highly active and selective catalysts for the bioorthogonal uncaging of propargylic and benzylic ether protected substrates, including uncaging in living E. coli . observed selectivity is supported by induced‐fit docking and molecular dynamics simulations. This proof‐of‐principle study points towards the utility of bioorthogonal enzyme/protecting group pairs for applications in the life sciences. Abstract : The great escape: Engineered cytochrome P450 monooxygenases were used for the removal of propargylic and benzylic ether protecting groups in vitro and in living E. coli . Deprotection resulted in the release of uncaged alcohols, which in this case display fluorescence properties. Such bioorthogonal enzyme/protecting group pairs could provide a means for the selective release of imaging agents or the catalytic activation of prodrugs at their site of action.